A Green Method to Fabricate Polyethyleneimine-Alginate Multilayer Coatings Modified Polyurethane Foam for Cu2+ Adsorption from Aqueous Solution. Issue 4 (4th March 2019) - Pan, Ying; Zhao, Hongting
ABSTRACT: In this study, flexible polyurethane foam (FPUF) was modified with bio-based coatings composed of polyethylenimine (PEI) and alginate (ALG), fabricated by layer-by-layer (LbL) self-assembly. LbL self-assembled coatings modified FPUFs were studied for their potentials for removing Cu 2+ ions from aqueous solutions by using batch adsorption technique, as a function of assembled bilayers number, pH value, carrier amount and adsorption time. The maximum adsorption capacity of the modified FPUF was shown to be 54 mg/g for Cu 2+ . Results suggested that the LbL self-assembly could potentially be a promising cost-effective technique for fabricating advanced adsorbent materials for removing pollutants from wastewater. GRAPHICAL ABSTRACT: